Spectroscopic Investigation of Chalcogen Bonding: Halide–Carbon Disulfide Complexes. Issue 9 (7th April 2021) - Haakansson, Christian T.; Corkish, Timothy R.; Watson, Peter D.; Robinson, Hayden T.; Tsui, Terrence; McKinley, Allan J.; Wild, Duncan A.
Abstract: A combined experimental and theoretical approach has been used to study intermolecular chalcogen bonding. Specifically, the chalcogen bonding occurring between halide anions and CS2 molecules has been investigated using both anion photoelectron spectroscopy and high‐level CCSD(T) calculations. The relative strength of the chalcogen bond has been determined computationally using the complex dissociation energies as well as experimentally using the electron stabilisation energies. The anion complexes featured dissociation energies on the order of 47 kJ/mol to 37 kJ/mol, decreasing with increasing halide size. Additionally, the corresponding neutral complexes have been examined computationally, and show three loosely‐bound structural motifs and a molecular radical. Abstract : Chalcogen bond strength is evaluated using a combination of experimental electron stabilisation energy and high‐level computational dissociation energy. Intermolecular dimer complexes of carbon disulfide with halides are studied using both anion photoelectron spectroscopy and CCSD(T) calculations, with the aim of uncovering the chalcogen bonding stabilising these complexes.